Catalytic atroposelective synthesis of axially chiral benzonitriles via chirality control during bond dissociation and CN group formation - Lv, Ya (2022)
The applications of axially chiral benzonitriles and their derivatives remain mostly unexplored due to their synthetic difficulties. Here we disclose an unusual strategy for atroposelective access to benzonitriles via formation of the nitrile unit on biaryl scaffolds pre-installed with stereogenic axes in racemic forms. Our method starts with racemic 2-arylbenzaldehydes and sulfonamides as the substrates and N-heterocyclic carbenes as the organocatalysts to afford axially chiral benzonitriles in good to excellent yields and enantioselectivities. DFT calculations suggest that the loss of p-toluenesulfinate group is both the rate-determining and stereo-determining step. The axial chirality is controlled during the bond dissociation and CN group formation. The reaction features a dynamic kinetic resolution process modulated by both covalent and non-covalent catalytic interactions. The axially chiral benzonitriles from our method can be easily converted to a large set of functional molecules that show promising catalytic activities for chemical syntheses and anti-bacterial activities for plant protections.